2022
DOI: 10.1097/jcma.0000000000000758
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of incidental thyroid carcinoma in euthyroid patients receiving total thyroidectomy for multinodular goiter: A retrospective cohort study

Abstract: Background: Total thyroidectomy is the treatment of choice for multinodular goiter (MNG). In some of these cases, incidental thyroid cancer (ITC) is detected postoperatively. Papillary thyroid microcarcinoma (PTMC), the most common type of ITC, has clinical factors and pathologic similarities with ITC that have not been well clarified previously. We investigated the incidence and characteristics of ITC and PTMC in euthyroid patients undergoing total thyroidectomy for MNG. Methods: We retrospectively investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…The post-operative hemorrhage in the Ligasure small jaw group was 39.80 ± 20.50 ml against 45.37±21.37 ml in the conventional method group. 25 In terms of blood loss Habash et al showed contrary findings to our study. Hemorrhage during surgery was assessed to be 42.13 ± 3.15 ml in Ligasure group and 73.50 ± 3.66 ml in conventional suturing group.…”
Section: Discussioncontrasting
confidence: 99%
“…The post-operative hemorrhage in the Ligasure small jaw group was 39.80 ± 20.50 ml against 45.37±21.37 ml in the conventional method group. 25 In terms of blood loss Habash et al showed contrary findings to our study. Hemorrhage during surgery was assessed to be 42.13 ± 3.15 ml in Ligasure group and 73.50 ± 3.66 ml in conventional suturing group.…”
Section: Discussioncontrasting
confidence: 99%
“…In the PTMC subset, Vasileiadis et al and Chen et al detected bilateral cancer foci in 19.4% and 28.1%, respectively, similar to the value found in our study (18.2%, 4/22) [ 29 , 36 ]. Finally, larger PTMCs seem more aggressive; hence, different diameters have been proposed as cut-off thresholds to distinguish different clinical courses [ 9 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this experience demonstrated a similar incidence of ITCs in the subset of cytological indeterminate thyroid nodules (46.8%, 22/47) as compared to the general population (45.2%, 127/281), suggesting that the coexistence of a class III/IV nodule does not increase the risk of having an ITC after surgery. Similarly, Chen et al found 41.2% of ITCs among BSRTC category III nodules [ 36 ]. Nonetheless, the evidence-based cancer risk in cytological categories III–IV turned out to be higher as compared to the expected risk rates reported in the BSRTC system (26.5% vs. 5–15% for class III and 31.3% vs. 15–30% for class IV) [ 12 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations